NHC-catalyzed cascade reaction between β-methyl enals and dienones for quick construction of complex multicyclic lactones - Sun, Jun (2021)
A NHC-promoted cascade reaction between β-methyl enal and dienone is developed for quick access to multicyclic lactone molecules bearing quaternary chiral carbon centers. Our study constitutes the first 1,6-addition of the acylazolium vinyl enolate γ-carbon via NHC catalysis and provides rapid access to complex lactone molecules that are otherwise difficult to prepare. The structurally sophisticated lactone products bearing up to four fused ring structures are afforded in up to quantitative yields with good to excellent enantioselectivities.